PI3K/Akt/Nrf2 mediated cellular signaling and virus-host interactions: latest updates on the potential therapeutic management of SARS-CoV-2 infection - Lekshmi, V. S.; Asha, Kumari; Sanicas, Melvin; Asi, Abhila; Arya, U. M.; Kumar, Binod (Frontiers in Molecular Biosciences, 2023)
The emergence and re-emergence of viral diseases, which cause significant global mortality and morbidity, are the major concerns of this decade. Of these, current research is focused majorly on the etiological agent of the COVID-19 pandemic, SARS-CoV-2. Understanding the host response and metabolic changes during viral infection may provide better therapeutic targets for the proper management of pathophysiological conditions associated with SARS-CoV-2 infection. We have achieved control over most emerging viral diseases; however, a lack of understanding of the underlying molecular events prevents us from exploring novel therapeutic targets, leaving us forced to witness re-emerging viral infections. SARS-CoV-2 infection is usually accompanied by oxidative stress, which leads to an overactive immune response, the release of inflammatory cytokines, increasing lipid production, and also alterations in the endothelial and mitochondrial functions. PI3K/Akt signaling pathway confers protection against oxidative injury by various cell survival mechanisms including Nrf2-ARE mediated antioxidant transcriptional response. SARS-CoV-2 is also reported to hijack this pathway for its survival within host and few studies have suggested the role of antioxidants in modulating the Nrf2 pathway to manage disease severity. This review article highlights the interrelated pathophysiological conditions associated with SARS-CoV-2 infection and the host survival mechanisms mediated by PI3K/Akt/ Nrf2 signaling pathways that can help ameliorate the severity of the disease and provide effective antiviral targets against SARS-CoV-2.